(untitled) (Bangladesh Journal of Agricultural Research, 2022)
The study was conducted in strawberry growing areas namely, Joypurhat and Rajshahi districts to examine the profitability of strawberry cultivation in Bangladesh. A total of 100 strawberry growing farmers were randomly selected for this study. Descriptive statistics and Cobb-Douglas (profit) function were used to analyze data. In the farm level 63% of the farmers’ cultivated strawberry in medium high land and majority of them mentioned the soil of their strawberry field was sandy loam (54%) and loam (35%). American Festival and Rabi-3 were found cultivating in the study areas. They performed some intercultural operations like weeding, spraying, and irrigating the crop. Per hectare cost of producing strawberry was estimated at Tk. 7, 30,811 and sapling cost was the major cost item which covered about 37% of total cost. Per hectare net return from strawberry cultivation were found Tk. 15, 57,355 and BCR was 3.13 which indicates strawberry cultivation is highly profitable. Farmers’ experience had positive and cost of hired labour, sapling and chemicals had negative influence on the profitability from strawberry farming. From the results of SWOT analysis it is observed that though it has strength and opportunities of cultivation in Bangladesh, it also has some weaknesses and threats. If the shortcomings are overcome, it is possible to increase strawberry cultivation in Bangladesh. Bangladesh J. Agril. Res. 45(1): 29-42, March 2020